USE OF E-BANKING IN ISLAMIC BANKS IN INDONESIA: Comparison of E-Banking Between Islamic Banks and Conventional Banks - Nurjannah, Afifah Zahroh; Santoso, Suryo Budi (Universitas Putera Batam, 2022)
This article focuses on the use of computer bases in making bank accounts at Islamic banks, and later on the data will be compared with existing data in conventional banks. This is because in banking, there are two types of banks based on their operational activities, namely Islamic banks and conventional banks. The research in this article is a qualitative study, because it requires various information from Islamic banks and conventional banks. From the information obtained related to Islamic banks and conventional banks, both types of banks have used E-Banking services to make it easier for their customers. However, there are some differences regarding the E-Banking services provided by each bank. So with the research in this article, it is expected to be able to provide information regarding the differences in E-Banking services that exist in Islamic banks and conventional banks. The results of this study are able to provide information related to what e-banking is used by conventional banks and Islamic banks.